2017
DOI: 10.1108/ijqrm-03-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma: yesterday, today and tomorrow

Abstract: Purpose The purpose of this paper is to share the experiences and perspectives of three practitioners from two continents on the subject of Lean Six Sigma (LSS) from both academic and industrial viewpoints. The authors of the paper have each been working on the topic of LSS over the past 15 years and have contributed over 150 journal and conference papers to the topics of lean and Six Sigma. Design/methodology/approach The approach is to synthesize the practical experiences and research conducted by three au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
229
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(247 citation statements)
references
References 44 publications
2
229
0
16
Order By: Relevance
“…In the literature, there are many studies examining the impact of the use of Six Sigma in the sustainability of organizations. They are focused on three major areas: (a) costs (cost reduction, reduction of defects, waste reduction, reducing waiting times, reducing unnecessary inventories) [18], (b) quality (increased quality products and services, reducing process variability) [19], and (c) satisfaction (accelerated delivery time, process and production cycle, increased customer and employee satisfaction) [20]. Chugani et al [15] found 70 articles that analyze the impact of Six Sigma on environmental sustainability.…”
Section: Six Sigmamentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, there are many studies examining the impact of the use of Six Sigma in the sustainability of organizations. They are focused on three major areas: (a) costs (cost reduction, reduction of defects, waste reduction, reducing waiting times, reducing unnecessary inventories) [18], (b) quality (increased quality products and services, reducing process variability) [19], and (c) satisfaction (accelerated delivery time, process and production cycle, increased customer and employee satisfaction) [20]. Chugani et al [15] found 70 articles that analyze the impact of Six Sigma on environmental sustainability.…”
Section: Six Sigmamentioning
confidence: 99%
“…The DMAIC structure (define-measure-analyze-improve-control) facilitates the statistical definition of a problem as well as its solution [20]. In this way, and because the whole process is based on data, subjectivity and arbitrariness are eliminated when making difficult decisions.…”
Section: Six Sigmamentioning
confidence: 99%
See 2 more Smart Citations
“…This is commonly known as a 1.5 sigma shift. So, the standardised definition of the Six Sigma quality considers this shift and guarantees that a six-sigma process will produce no more than 3.4 DPMO (Antony, Snee & Hoerl, 2017;Harry, 1988).…”
Section: Citibank Groupmentioning
confidence: 99%